Unveiling Rarity: A Case Report on Mucoepidermoid Carcinoma of Lung - Aneeta Singh; KC Goswami; Shalija Kotwal; Avinash Rajra (JK Science)
Primary salivary gland-type tumours of the lung (PSGT) are very rare and constitute less than 1% of all primary lung tumours and commonest subtype of PSGT is pulmonary mucoepidermoid carcinoma (PMEC). We present such a case in 28-year-old male with history of fever, haemoptysis and dyspnoea, he had gross pallor, thin built and his x-ray showed opacity in left lower zone. His CECT chest showed endobronchial mass and PET-CT was suggestive of bronchial carcinoid. Final diagnosis of PSGT was confirmed with help of histopathology and immuno-histochemistry. We aim to emphasize the importance of this rare tumour as close differential of carcinoid tumour.